Adaptations to Opioid Use Disorder Care During the COVID-19 Pandemic: A National Survey of Prescribers. Issue 5 (11th September 2022) - Sung, Minhee L.; Black, Anne C.; Blevins, Derek; Henry, Brandy F.; Cates-Wessel, Kathryn; Dawes, Michael A.; Drexler, Karen; Hagle, Holly; Molfenter, Todd; Levin, Frances R.; Becker, William C.; Edelman, E. Jennifer
Abstract : Objectives: Among opioid use disorder (OUD)-treating providers, to characterize adaptations used to provide medications for OUD (MOUD) and factors associated with desire to continue virtual visits post-COVID-19 pandemic. Methods: In a national electronic survey of OUD-treating prescribers (July-August 2020), analyses restricted to X-waivered buprenorphine prescribers providing outpatient, longitudinal care for adults with OUD, quantitative and qualitative analyses of survey items and free text responses were conducted. Results: Among 797 respondents, 49% were men, 57% ≥50 years, 76% White, 68% physicians. Respondents widely used virtual visits to continue prescribing existing MOUD regimens (79%), provide behavioral healthcare (71%), and initiate new MOUD prescriptions (49%). Most prescribers preferred to continue/expand use of virtual visits after COVID-19. In multivariable models, factors associated with preference to continue/expand virtual visits to initiate MOUD postpandemic were treating a moderate number of patients prepandemic (aOR = 1.67; 95%[CI] = 1.06, 2.62) and practicing in an urban setting (aOR = 2.17; 95%[CI] = 1.48, 3.18). Prescribing buprenorphine prepandemic (aOR = 2.06; 95%[CI] = 1.11, 3.82) and working in an academic medical center (aOR = 2.47; 95%[CI] = 1.30, 4.68) were associated with preference to continue/expand use of virtual visits to continue MOUD postpandemic. Prescribing naltrexone extended-release injection prepandemic was associated with preference to continue/expand virtual visits to initiate and continue MOUD (aOR = 1.51; 95%[CI] = 1.10, 2.07; aOR = 1.74; 95%[CI] = 1.19, 2.54). Qualitative findings suggest that providers appreciated virtual visits due to convenience and patient accessibility, but were concerned about liability and technological barriers. Conclusions: Surveyed prescribers widely used virtual visits to provide MOUD with overall positive experiences. Future studies should evaluate the impact of virtual visits on MOUD access and retention and clinical outcomes.